The role of obesity and Type 2 diabetes in lung health: A systematic review (2024) - Roanne Lecky; Svitlana Grogan; Priyank Shukla; Sarah Atkinson; Paula L. McClean; Catriona Kelly (PLoS ONE, 2026)
Introduction Type 2 diabetes is associated with mild airways restriction, yet obstructive lung conditions are prevalent in people with diabetes. Obesity is a confounding factor and has been reported to be both protective and to enhance risk of lung disease independent of hyperglycaemia. The aim of this systematic review was to evaluate how Type 2 diabetes and obesity affect lung function measurements in people with and without chronic obstructive pulmonary disease (COPD) and asthma. Methods Ovid MEDLINE and Embase databases were methodically searched for studies published between 2011–2024. Ninety-three studies were included, with 35,891 participants. Included studies had data on Type 2 diabetes and/or obesity and forced expiratory volume in one second (FEV1) and/or forced vital capacity (FVC). All studies were assessed for quality (Newcastle-Ottawa scale) or risk of bias (Cochrane methodology). Data was extracted as combined means and standard deviation, and significance tested by Kruskal-Wallis. Multiple linear regression was conducted to account for the impact of age, BMI, Type 2 diabetes and geographical region. Results Those with Type 2 diabetes without a lung disease had mild airway restriction. However, outcomes for those with asthma and COPD in the presence of Type 2 diabetes were largely comparable to those who had either condition in the absence of Type 2 diabetes. A Type 2 diabetes diagnosis and being in the geographical region of Asia were significantly associated with decreased FEV1 and FVC, but obesity was not. The study is limited by the large number of cross-sectional studies using single time points from which conclusions on causality cannot be drawn. Conclusion Type 2 diabetes is independently associated with airways restriction suggesting that monitoring of lung function following a diabetes diagnosis may be warranted.